ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PENGUNGKAPAN LAPORAN PERUSAHAAN YANG BERBASIS DARING ATAU WEB PADA PT. JASA MARGA KUALANAMU TOL - Nur Asmalia; Aried Sumekar (Worksheet : Jurnal Akuntansi, 2021)
Preparation of financial reports using this online or web method aims to make iteasier for employees to make financial reports using the Internet or web media. Theinternet is widely used by various groups of people to facilitate a job, be it a job inthe financial or non-financial fields. The internet also helps to disseminateinformation and communication of a company, especially in the financial sector, sothat outside investors can find out about the company's financial developments inan effective and efficient manner. The media for delivering this information isknown as IFR (Internet Financial Reporting). The method in preparing thesefinancial statements is the method of profitability, leverage, and liquidity. This datacollection method is by doing a 7-day risert at the company PT. JasamargaKualanamu Tol as well as data sources from libraries and employees at thecompany through interviews. This online financial report preparation can be saidto be successful if the investors out there are enthusiastic about the company'sfinancial statements.